Taxonomic study on selected species of stingless bees (Hymenoptera: Apidae: Meliponini) in Sulawesi Island, Indonesia - MANAP TRIANTO; TUTY ARISURYANTI; HARI PURWANTO; ROSICHON UBAIDILLAH (Society for Indonesian Biodiversity, 2024)
Abstract. Trianto M, Arisuryanti T, Purwanto H, Ubaidillah R. 2024. Taxonomic study on selected species of stingless bees (Hymenoptera: Apidae: Meliponini) in Sulawesi Island, Indonesia. Biodiversitas 25: 2290-2306. Stingless bees are strong candidates as alternative crop pollinators. They are found throughout the tropics, with the exception of the Pacific islands. There are three tropical regions in the world, namely the tropical Americas (Neotropic), Sub-Saharan Africa (Afrotropic), and Indoaustralian (Austroasiatic) region. In this research, we explored the morphological and morphometric characteristics of stingless bees in Sulawesi Island, Indonesia. The genera and species identification of stingless bees were based on morphological characters and coloration, such as the structure and color of the antenna, head, thorax, wing, leg and abdomen. Morphological and morphometric identification of 10 species of stingless bees consisting of five genera, namely the genera Heterotrigona, Homotrigona, Lepidotrigona, Tetragonula, and Wallacetrigona. The genus Tetragonula consists of six small species (<4 mm), namely T. biroi, T. clypearis, T. fuscobalteata, T. laeviceps, T. pagdeni, and T. sapiens. The genera Heterotrigona, Homotrigona, Lepidotrigona, and Wallacetrigona are a group of large stingless bees (>4 mm), each consisting of one species, namely H. itama, H. canifrons, L. terminata, and W. incisa. H. itama and H. canifrons are new records on Sulawesi Island. These species are found in Lore Lindu National Park (TNLL). Until 2023, these species were only found in Java, Kalimantan and Sumatra. This research can be used as a guide in the identification and validation of stingless bee species on Sulawesi Island.